An Ethical Dilemma Between Free Speech And Hate Speech: A Case Study Of Sri Lanka Under The International Covenant On Civil And Political Rights (Iccpr) Act - Aznee Ahamed, M. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
Freedom of speech and expression is a Fundamental Human Right recognized in numerous international treaties, including the International Covenant on Civil and Political Rights (ICCPR). However, freedom of speech is not unlimited and can be subject to lawful restrictions, including prohibitions against hate speech, which the ICCPR also acknowledges. As a state party to the Covenant, Sri Lanka is obligated under Article 2 of the ICCPR to protect and promote the rights outlined in the Covenant within its jurisdiction, without any form of discrimination. In fulfilling its obligations, Sri Lanka enacted the ICCPR Act which includes provisions to prohibit hate speech. This research seeks to investigate whether the ICCPR Act of Sri Lanka has been implemented in the true spirit of the ICCPR provisions to protect civil and political rights or if it has been applied in a manner that undermines these rights, thereby breaking the spirit of the ICCPR, specifically focusing on the ethical dilemma between hate speech and free speech. The research adopts a qualitative method using primary and secondary data sources. It has the primary objective to examine case laws and reported incidents under the ICCPR Act and to provide recommendations for the improved application of the Act. Laws that restrict free speech must be narrowly defined and strictly interpreted to prevent misuse. Section 3(1) of the ICCPR Act mirrors Article 20 (1) and (2) of the Covenant, which offers a broad definition. However, well-structured guidelines like the Rabat Plan of Action and the Strategy and Plan of Action on Hate Speech provide international frameworks for applying hate speech prohibitions, which Sri Lanka lacks. It has led to wide prosecutorial discretion, resulting in selective enforcement against minority communities and the politicization in the application of the Act. Consequently, the hate speech restrictions under the Act undermine freedom of speech and violate the spirit of the ICCPR. Thus, Sri Lanka has failed to fulfil its obligations under the ICCPR. The researcher primarily recommends formulating and implementing proper guidelines that incorporate international standards for prohibiting hate speech, thereby limiting prosecutorial discretion under the ICCPR Act to maintain a balance between free speech and prohibition of hate speech.
Keywords: Free speech; Hate speech; ICCPR; ICCPR act; Prosecutorial discretion